EFFECTS OF PEROXYNITRITE SCAVENGERS ON OXIDATIVE METABOLISM IN PERIODONTAL TISSUES OF RATS UNDER EXCESSIVE COMBINED SODIUM NITRATE AND FLUORIDE INTAKE - Bogdanov, A.V.; Kostenko, V.A. (World of Medicine and Biology, 2016)
This research aimed to study the effects of peroxynitrite scavengers (L-selenomethionine and uric acid) on oxidative (NO-synthase) pathway of L-arginine metabolism, the level of superoxide anion radical production, lipid peroxidation (LPO) and antioxidant (AO) protection in the soft tissues of periodontium under excessive combined sodium nitrate and fluoride intake in 50 white rats. It has been found out the use of L-selenomethionine in experimental conditions reduces the total NO-synthase activity, production of superoxide anion radical by NADPH- and NADH-dependent electron transport chains as well as by leukocyte NADPH oxidase in the periodontal tissues; limits the LPO and increases the antioxidant potential. Introduction of uric acid decreases the total NO-synthase activity, production of superoxide anion radical by mitochondrial respiratory chain and lipid peroxidation, and increases the catalase activity in the periodontal tissues.
Keywords: peroxynitrite scavengers; NO-synthase; superoxide anion radical; lipid peroxidation; antioxidant system; periodontium